2021
DOI: 10.3389/fvets.2021.597949
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Body Weight-Supported Treadmill Training and Conventional Over-Ground Training in Dogs With Incomplete Spinal Cord Injury

Abstract: In human medicine there was no evidence registered of a significant difference in recovery between body weight-supported treadmill training (BWSTT) and conventional over-ground (COGI). There isn't any similar study in veterinary medicine. Thus, this study aimed to compare the locomotor recovery obtained in incomplete SCI (T11–L3 Hansen type I) post-surgical dogs following BWSTT or COGI protocols, describing their evolution during 7 weeks in regard to OFS classifications. At admission, dogs were blindly randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Compared to the present study, the results described above may be related to the fact that locomotor training should be performed every day in order to induce plasticity in the reflex pathways [ 17 , 126 , 139 , 140 ]. In Martins et al (2020) [ 17 ], the authors reported a statistically significant positive evolution over time, with an increase in mean OFS related to the locomotor training implemented.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Compared to the present study, the results described above may be related to the fact that locomotor training should be performed every day in order to induce plasticity in the reflex pathways [ 17 , 126 , 139 , 140 ]. In Martins et al (2020) [ 17 ], the authors reported a statistically significant positive evolution over time, with an increase in mean OFS related to the locomotor training implemented.…”
Section: Discussionmentioning
confidence: 67%
“…Compared to the present study, the results described above may be related to the fact that locomotor training should be performed every day in order to induce plasticity in the reflex pathways [ 17 , 126 , 139 , 140 ]. In Martins et al (2020) [ 17 ], the authors reported a statistically significant positive evolution over time, with an increase in mean OFS related to the locomotor training implemented. Thus, repetitive locomotor training tasks could promote cutaneous reflex excitability [ 141 ], by different mechanisms, such as the sprouting and regeneration of damaged fibers and changes in synapses’ efficiency [ 142 , 143 ].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Furthermore, electrical stimulation by FES may potentiate large-diameter motor neurons recruitment capable of fast conduction velocity fibers instead of recruiting small diameter motor neurons, which are slower and more susceptible to fatigue [ 101 , 102 ]. FES may also increase the muscle tonus in the hindlimbs and enhance the polysynaptic reflex, essential in this population of dogs that showed an absent or decreased withdrawal reflex [ 66 , 67 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%